(untitled) (GYMNASIUM, 2017)
Connecting a brand to Olympic Games through sponsorship contributes to the build of a competitive advantage and maps a positive image in the long run. Brand awareness is considered to be the first necessary stage in the demanding process towards achieving purchase and brand commitment. The research evaluates the post-2004 Olympic sponsorship reality in Athens presenting a series of different brand awareness scenarios, hopefully contributing towards understanding the process of brand image building and preservation. The random sample N = 400 was generated through a tailor made questionnaire. Overall, the results demonstrate high long term awareness levels for sponsoring brands which continued to increase in the different stages of questioning and maximized in the last level where respondents had to choose between competitors. On the other hand, challenges were found in the ‘fit’ between the sponsoring brand’s image and the Olympic sponsorship setting leading to low levels of brand awareness. In total, the study could suggest a useful tool to be used in other post – event localities producing generalizable results and conclusions.